Implementasi Profil Pelajar Pancasila dalam Membentuk Karakter Peserta Didik Sekolah Dasar - Dewi, Rulynda Tiara; Ardhyantama, Vit; Khalawi, Hasan (PGSD STKIP PGRI Pacitan, 2024)
This study aims to determine: (1) the implementation of the Pancasila Student Profile in developing the character of students at elementary school, (2) the supporting factors for the implementation of the Pancasila Student (3) The inhibiting factors for the implementation of the Pancasila Student Profile. This research is qualitative research with a descriptive approach. The data collection techniques used in this study were observation, interviews and documentation. Data analysis techniques use model Miles and Huberman. The results of the data analysis showed that: (1) Implementation of the Profile Implementation of the Pancasila Student Profile in developing the character students at SD Negeri 2 Baleharjo was carried out well. This is evident from the implementation, starting from learning, habituation, extracurricular, and co-curricular activities, which make students characters according to Pancasila values. (2) Factors supporting the implementation of Pancasila student profiles are good facilities and infrastructure, teaching staff who follow the driving teacher program, and a comfortable and conducive learning environment. (3) Factors inhibiting the implementation of Pancasila student profiles are the teacher's limitations in preparing lesson plans, the teacher's rules in using IT media and various learning resources, and the decreased interest in student learning.